Performance of PROMIS Physical Function, Pain Interference, and Depression Computer Adaptive Tests Instruments in Patients Undergoing Meniscal Surgery - Yining Lu, M.D; Alexander Beletsky, B.A; Benedict U. Nwachukwu, M.D., M.B.A; Bhavik H. Patel, B.S; Kelechi R. Okoroha, M.D; Nikhil Verma, M.D; Brian Cole, M.D., M.B.A; Brian Forsythe, M.D (Elsevier, 2020)
Purpose: To compare the performance of the Patient-Reported Outcomes Measurement Information System (PROMIS) physical function (PF), pain interference (PIF), and depression computer adaptive tests (CAT) relative to legacy instruments in patients undergoing meniscal surgery. Methods: Patients scheduled to undergo meniscal surgery completed legacy knee function PROMs (International Knee Documentation Committee [IKDC], Knee Injury and Osteoarthritis Outcome Score [KOOS] subscores), Marx Activity Rating Scale (MARS), Veterans-Rand 12 (VR12), Short Form 12 (SF12), and the Brief Resilience Scale (BRS) alongside PROMIS PF, PIF, and Depression preoperatively. Spearman rank correlations were calculated, and score distributions were examined for floor and ceiling effects. Results: 152 patients (46.6 ± 14.9 years, 67.1% male) completed PROMs for appropriate inclusion. PROMIS PF yielded high-moderate to high correlations with the IKDC and KOOS subscales (r = 0.61 to 0.73), demonstrating similar performance to the IKDC. PROMIS PIF demonstrated moderately high-moderate to high correlations with the IKDC, KOOS subscales, VR-12 Physical Component Score (PCS), and SF12 PCS (r = 0.62 to 0.71), performing comparably to KOOS Pain (r = 0.55 to 0.92). PROMIS Depression demonstrated moderate to high-moderate correlations with the mental health legacies (r = 0.46 to 0.66). Significant ceiling effects were observed for MARS (n = 29, 18.8%), and significant floor effects were exhibited by PROMIS Depression (n = 38, 25%) and MARS (n = 27, 17.6%). Conclusion: The PROMIS PF, PIF CAT, and Depression instruments exhibit comparable performance profiles relative to legacy knee PROMs. PROMIS PF and PIF demonstrated no floor and ceiling effects, whereas PROMIS Depression exhibited a significant relative floor effect. PROMIS PF and PIF may be appropriately used to establish functional baselines preoperatively. Level of Evidence: IV, diagnostic case series.